2013
DOI: 10.1080/00103624.2013.841919
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Organic Nutrient Management Fosters the Eubacterial Community Diversity in the Indian Semi-arid Alfisol as Revealed by Length Heterogeneity–PCR

Abstract: Agricultural practices influence the community structure and functional diversity of soil microorganisms. In the present study, the impact of nutrient-management systems on the changes in the biological properties of Indian semi-arid Alfisol was assessed. The long-term organically managed (OGF) and inorganically fertilized (IGF) soils from century-old experimental plots were compared for eubacterial diversity using amplicon length heterogeneity PCR (LH-PCR) targeting three hypervariable domains (V1, V1_V2, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The influence of the molecular ecology and culturing method on the diversity, composition and dynamics of the microbial community have been investigated using cell cultures, colony counting, denaturing gradient gel electrophoresis [9,10], temperature gradient gel electrophoresis [1113], microarray [14] and length heterogeneity polymerase chain reaction [15,16]. However, a complete understanding of the microbial community remains elusive [17].…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the molecular ecology and culturing method on the diversity, composition and dynamics of the microbial community have been investigated using cell cultures, colony counting, denaturing gradient gel electrophoresis [9,10], temperature gradient gel electrophoresis [1113], microarray [14] and length heterogeneity polymerase chain reaction [15,16]. However, a complete understanding of the microbial community remains elusive [17].…”
Section: Introductionmentioning
confidence: 99%
“…We measured these six variables from four long-term nutrient management adopted soils (control, inorganic fertilizer-applied, organic manure amended, and integrated nutrient management adopted). Based on the literature and our previous works, the continuous use of organic and inorganic nutrient amendments could significantly alter the above mentioned biological attributes and largely SOC (Preethi et al, 2012;Chinnadurai et al, 2013;Balachandar et al, 2014;Chinnadurai et al, 2014;Tamilselvi et al, 2015;Balachandar et al, 2016). All these biological attributes were reported highest in INM and OM, whereas the IC and control recorded on par values or sometimes IC was higher than control.…”
Section: Soil Biological Attributes and Soil Biological Quality Indexmentioning
confidence: 90%
“…Our ndings also showed that resource conservation practices have higher microbial biomass carbon (MBC) content compared to CC (Table 2). Balanced nutrient inputs and supplemented by resource conservation practices play a crucial role for enhancement of soil organic carbon (SOC) and MBC (Cookson et al, 2007;Balachandar et al, 2014). The higher content of MBC in green manuring treatment might be due to presence of higher shoot and root biomass turn- over (Mandal et al, 2007;Liu et al, 2013;Shahid et al, 2017), which signi cantly increases carbon input (Manna et al, 2005;Lal, 2015).…”
Section: Impact Of Resource Conservation On Soil Carbon and Nitrogen Fractionsmentioning
confidence: 99%